Adaptive tutoring system user preferences: Does gender matter? - Faizal Hazri, Mat Ripin; Rahmah, Mokhtar; Wahidah, Mohd Zain (IEEE, 2017)
The adaptive tutoring system is one of the applications in teaching and learning processes, providing worldwide accessibility and all-day availability. Apparently, studies on user preference across gender for adaptive tutoring systems remain scarce among university users in Malaysia. With the aim of describing the differences between genders in user preferences for the method of gaining information, online games, online movies, online music, pictures, as well as colors of the adaptive tutoring system, this paper used quantitative methods through data gathering for finding the results of this study. Sixty-eight respondents were chosen from among academicians, administrative staff and students of a public university in Malaysia. Descriptive analysis of the data shows that there exists a pattern of different preferences for adaptive tutoring systems across gender. This paper provides data supporting the need to design different interfaces for male and female users.